Genetic variants in levodopa-induced dyskinesia (LID): A systematic review and meta-analysis. (March 2021) - Falla, Marika; Di Fonzo, Alessio; Hicks, Andrew Anthony; Pramstaller, Peter Paul; Fabbrini, Giovanni
Abstract: Introduction: Levodopa-induced dyskinesia frequently complicates long-term Parkinson's disease. More in-depth knowledge regarding the role of genetic factors in dyskinesia development may be important to identify parkinsonian patients who are more prone to developing dyskinesia and clarify the molecular mechanisms underlying this condition. For this reason, we systematically reviewed studies investigating genetic factors involved in dyskinesia. Methods: A systematic search of genetic factors in Parkinson's disease dyskinesia was performed using the MEDLINE (through PubMed up to June 2019) and EMBASE databases according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A meta-analysis was conducted using a random effect model. Results: The literature search retrieved 33 studies assessing genes and variants possibly associated with dyskinesia in Parkinson's disease. The studies were published between 1984 and 2019 and included a total of 27, 092 subjects of different ethnicities. Overall, 37 genes were analyzed in the studies reviewed, of which 22 were possibly associated with dyskinesia. The studies reported a total of 158 variants, of which 94 were possibly related to dyskinesia. Conclusion: The studies reviewed demonstrated inconsistent results, possibly due to differences in screening methods and in the comparison of clinical data in a large variety of genetically- and ethnically-diverse populations. The meta-analysis failed to demonstrate any association between the rs6280 in the DRD3 gene, rs1799836 in the MAO-B, rs4680 in the COMT gene, rs34637584 in the LRRK2 gene and LID susceptibility. The role of genetic factors in LID susceptibility is still unclear and further studies are required. Highlights: 12 genes have been found to be potentially linked to LID in Parkinson's disease. Genetic basis of LID may be related to the genes implicated in dopamine- or non-dopamine-mediated neurotransmission or the genetic factors implicated in genetic parkinsonism. The studies reviewed demonstrate inconsistent and contradictory results due to different methodologies and methods of assessment of LID and other factors. The role of genetic factors in LID susceptibility remains unclear and further studies are required. Future research should verify whether possessing multiple genetic variants in clusters of genes considered "at risk" increases the significance of the association with LID.